Surface treatment method of magnesium alloy, magnesium alloy part and application of magnesium alloy part
By preparing a microarc oxide film layer on the surface of the magnesium alloy and coating conductive coating, the problem of insufficient conductivity and corrosion resistance of magnesium alloy in fuel cells is solved, and the conductivity and corrosion resistance are improved. It is suitable for fuel Battery and aerospace fields.
Patent Information
- Application Number
- CN202411378650.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2024-12-27
AI Technical Summary
When magnesium alloys are used as bipolar plate materials in fuel cells, there are problems such as decreased conductivity and insufficient corrosion resistance, which leads to low stability and high cost in harsh environments.
Using the composite technology of microarc oxide film layer and conductive coating, the microarc oxide film layer is prepared on the surface of magnesium alloy and coated with conductive coatings, including conductive polymers or carbon nanotubes, to improve magnesium The conductivity and corrosion resistance of the alloy.
It has achieved improved conductivity and corrosion resistance of magnesium alloys, reduced the contact resistance of bipolar plate surface interface, reduced the weight of fuel cells, and is suitable for aerospace and other fields, improving the overall performance and application breadth of magnesium alloys.
Smart Images

Figure CN119194560A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of surface treatment, and in particular relates to a surface treatment method of a magnesium alloy, a magnesium alloy part and applications thereof. Background Art
[0002] In recent years, due to the extensive use of fossil energy, energy depletion, environmental pollution and other problems have become increasingly serious. Hydrogen energy, as an environmentally friendly energy source, has been increasingly used as a substitute for fossil fuels. Fuel cells, as a power generation device, can directly convert non-polluting fuels (such as hydrogen energy) into electrical energy through chemical energy. Proton exchange membrane fuel cells (PEMFC) have been widely used in transportation, power stations, mobile power supplies, military fuel cells and other fields due to their advantages such as high energy conversion rate, fast start-up, low noise and environmental friendliness.
[0003] As one of the key components in proton exchange membrane water electrolysis hydrogen production, bipolar plates provide gas reaction sites, collect current, support membrane electrodes, and manage water. Bipolar plates are required to have high corrosion resistance, low interface resistivity, good mechanical strength, hydrophobicity, and anti-oxidation performance. The current bipolar plate materials mainly include graphite materials, composite materials, and metal materials. Graphite bipolar plates have low mechanical strength, complex manufacturing processes, and high volume power density; composite bipolar plates have simple manufacturing processes and strong corrosion resistance, but poor conductivity. Metal bipolar plates have the advantages of low cost, easy manufacturing, high power density, and good mechanical properties, which are suitable for mass production. They are currently the preferred electrode plate material for fuel cell industrialization.
[0004] Bipolar plates account for 80% of the volume, 70% of the mass and 29% of the cost of the fuel cell stack. Developing low-density metal bipolar plates to prepare lightweight fuel cells has become a trend in the future development of fuel cells. The bipolar plates made of metal materials such as aluminum, nickel, titanium and stainless steel currently used have high density and high cost, which can hardly meet the needs of lightweight fuel cells.
[0005] As the lightest metal structural material, magnesium alloy has high specific strength and specific stiffness, good electrical and thermal conductivity, excellent anti-electromagnetic interference and biocompatibility. It has important application value and broad application prospects in the fields of automobiles, aerospace, electronics, biomedicine, etc. However, poor corrosion resistance is one of the main obstacles limiting its widespread application in industrial products.
[0006] Therefore, how to effectively and reasonably improve the corrosion resistance of magnesium alloys has become one of the focuses of current magnesium alloy application research. Improving the corrosion resistance of magnesium alloys can be carried out from two aspects: on the one hand, starting from the magnesium alloy itself, developing new magnesium alloys with excellent performance; on the other hand, improving the corrosion resistance and wear resistance of magnesium alloys through effective surface treatment. Numerous research results show that the corrosion resistance of magnesium alloys can be improved by changing the chemical composition and organizational structure of magnesium alloys, but the changes in the composition and organization of magnesium alloys are generally accompanied by the addition of heavy rare earth elements, which makes the density of magnesium alloys increase significantly, which reduces the advantages of magnesium alloy applications. Therefore, in order not to change the low-density advantage of magnesium alloys, the surface properties of magnesium alloys can be changed through surface technology to improve their corrosion resistance.
[0007] Common magnesium alloy surface treatment methods include anodizing, chemical plating / electroplating, micro-arc oxidation, organic film layer, conductive / chemical oxidation, etc. Among them, micro-arc oxidation can form a ceramic layer with metal oxide as the main phase, controllable thickness and good bonding with the substrate on the surface of the magnesium alloy by adjusting the composition of the electrolyte and controlling the corresponding power supply mode and electrical parameters, which improves the corrosion resistance of the magnesium alloy substrate to a certain extent. However, the hydrophilic micro-arc oxidation film layer has structural defects such as micropores and microcracks on the surface, which can only provide passive corrosion protection for the magnesium alloy substrate. At the same time, the micro-arc oxidation film layer sacrifices the good electrical conductivity of the magnesium alloy itself due to its high insulation, thereby limiting the application of magnesium alloy micro-arc oxidation products in aerospace, electronic products and other fields.
[0008] In the aerospace field, in order to meet actual production requirements, some parts use a composite surface treatment method of local conductive oxidation and micro-arc oxidation, which is a complex process, time-consuming and costly. In addition, in the working environment of the battery, magnesium alloys will not only form a passivation film on the surface, causing high surface resistance, but also be easily oxidized, resulting in a decrease in the conductivity of the battery. The magnesium alloy bipolar plates corroded by oxidation are difficult to work stably and need to be replaced in a timely manner in severe cases, resulting in a decrease in the conductivity of the fuel cell, low stability in use, and high cost. Therefore, magnesium alloys as bipolar plate materials are currently only in the theoretical stage. Summary of the invention
[0009] The problem to be solved by the present invention is to provide a surface treatment method for a magnesium alloy, a magnesium alloy part and application thereof, so as to simultaneously improve the electrical conductivity and corrosion resistance of the magnesium alloy.
[0010] The present invention includes a surface treatment method for a magnesium alloy, comprising the following steps: S1. Preparing a micro-arc oxidation film on the surface of a magnesium alloy; S2. preparing a conductive coating; the conductive coating comprises a conductive polymer or carbon nanotubes; S3. Coating the conductive coating obtained in S2 on the surface of the micro-arc oxidation film layer obtained in S1 to obtain a composite film layer.
[0011] As a general inventive concept, the present invention also includes a magnesium alloy part prepared by the above-mentioned magnesium alloy surface treatment method.
[0012] As a general inventive concept, the present invention also includes the use of a magnesium alloy part in a proton exchange membrane fuel cell, where the magnesium alloy part is used as a magnesium alloy bipolar plate of the proton exchange membrane fuel cell.
[0013] Beneficial effects of the present invention: The present invention uses a magnesium alloy with extremely low density as a substrate, and prepares a conductive and corrosion-resistant composite film layer on the surface of the substrate through micro-arc oxidation treatment and coating with a conductive coating. The micro-arc oxidation film layer has good corrosion resistance, but because it has high insulation, it sacrifices the good conductivity of the magnesium alloy itself. Therefore, the present invention further prepares a conductive layer on the basis of the micro-arc oxidation film layer. The conductive layer is coated with a conductive coating prepared by using conductive carbon nanotubes or conductive polymers, and finally forms a conductive and corrosion-resistant composite film layer on the surface of the magnesium alloy, so that the treated magnesium alloy has both corrosion resistance and conductivity.
[0014] After research, the present invention has found that the micro-arc oxidation film has good surface morphology and roughness, which provides a better adhesion base for the coating of the conductive coating, ensuring the stability and durability of the film during use; and, the conductive film is prepared on the surface of the micro-arc oxidation film by direct coating, without the need for conductive preparation, which adapts to the high insulation characteristics of the micro-arc oxidation film, and can achieve full coverage of the micro-arc oxidation film with the conductive coating, and obtain a composite film with a coherent appearance. In addition, the surface treatment method provided by the present invention can also selectively perform local coating on the surface of the micro-arc oxidation film. Combined with the high insulation characteristics of the micro-arc oxidation film, the uncoated area has insulation and the coated area has conductivity, thereby meeting the local conductivity requirements of magnesium alloy parts and can adapt to different application scenarios.
[0015] The surface treatment method of the present invention has a simple preparation process, few operation steps, safety and environmental protection, is suitable for large-sized magnesium alloy structural parts, is not limited to the size of the structural parts, and enhances industrial application. The magnesium alloy conductive corrosion-resistant layer prepared by the present invention can reduce the surface interface contact resistance of the bipolar plate and enhance the corrosion resistance. Compared with existing metal materials such as aluminum, nickel, titanium and stainless steel, it can greatly reduce the weight of the proton exchange membrane fuel cell. In addition, the conductive corrosion-resistant layer prepared by the present invention is also suitable for magnesium alloy structural parts for aerospace. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Attached Figure 1 This is a flow chart of a magnesium alloy surface treatment method in one embodiment of the present invention; Attached Figure 2 The macroscopic morphology of the magnesium alloy micro-arc oxidation film layer and the magnesium alloy micro-arc oxidation-polyaniline composite film layer prepared in Example 1 of the present invention, wherein (a) is the magnesium alloy micro-arc oxidation film layer, and (b) is the magnesium alloy micro-arc oxidation-polyaniline composite film layer; Attached Figure 3 The potentiodynamic polarization curves of the magnesium alloy micro-arc oxidation film layer and the magnesium alloy micro-arc oxidation-polyaniline composite film layer prepared in Example 1 of the present invention; Attached Figure 4 These are macroscopic morphology pictures of the magnesium alloy micro-arc oxidation film and the magnesium alloy micro-arc oxidation-carbon nanotube composite film prepared in Example 2 of the present invention, wherein (a) is the magnesium alloy micro-arc oxidation film; and (b) is the magnesium alloy micro-arc oxidation-carbon nanotube composite film. DETAILED DESCRIPTION
[0017] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific implementation methods. It should be understood that the specific implementation methods described herein are only used to explain the present invention and are not intended to limit the present invention.
[0018] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art to which the present invention belongs. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items. In addition, the technical solutions between the various embodiments of the present invention can be combined with each other, but it must be based on the ability of ordinary technicians in the field to implement. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such combination of technical solutions does not exist and is not within the scope of protection required by the present invention.
[0019] Unless otherwise specified, all drugs / reagents used were commercially available.
[0020] An embodiment of the present invention provides a surface treatment method for a magnesium alloy, comprising the following steps: S1. Preparing a micro-arc oxidation film on the surface of a magnesium alloy; S2. preparing a conductive coating; the conductive coating comprises a conductive polymer or carbon nanotubes; S3. Coating the conductive coating obtained in S2 on the surface of the micro-arc oxidation film layer obtained in S1 to obtain a composite film layer.
[0021] In the embodiment of the present invention, a magnesium alloy with extremely low density is used as a substrate, and a conductive and corrosion-resistant composite film layer is prepared on the surface of the substrate by micro-arc oxidation treatment and coating with a conductive coating.
[0022] Conductive coatings include conductive polymers (such as polyaniline, polypyrrole, etc.) or carbon nanotubes, which can provide conductivity while enhancing the corrosion resistance of the material. Conductive polymers have good conductivity and can form a continuous conductive network in the film layer, which allows the surface of the film layer to conduct current, thereby giving magnesium alloys conductive properties. The film layer can effectively dissipate static charges, prevent sparks or other hazards caused by static electricity accumulation, and provide additional safety in certain applications. At the same time, the conductive polymer itself also has certain anti-corrosion properties and can form a protective passivation layer on the metal surface to reduce the rate of electrochemical corrosion. Furthermore, nano-oxides can be added to the conductive coating as corrosion inhibitors to fill the micropores and defects of the micro-arc oxidation film layer, thereby further enhancing the density of the composite film layer. These nanoparticles also have a barrier effect and can delay the diffusion of corrosive media.
[0023] The present invention combines a micro-arc oxidation film layer and a conductive coating to prepare a composite film layer, wherein the micro-arc oxidation film layer provides primary protection, blocks most of the corrosive media, and delays the occurrence of corrosion. At the same time, the conductive coating further fills the micropores and defects of the micro-arc oxidation film layer, increases the compactness of the overall system, and provides additional corrosion inhibition and protection effects. The corrosion inhibitor that can be added to the conductive coating slows down the further invasion of the corrosive medium. The micro-arc oxidation film layer itself is not conductive, but through the coverage of the conductive film layer, the conductive film layer provides a conductive network for the entire system, giving the magnesium alloy a conductive function, and the magnesium alloy as a whole can maintain good conductivity, and the electronic conductivity of the conductive polymer enables the film layer to provide protection while not affecting the electrical properties of the overall material. The micro-arc oxidation film layer and the conductive film layer synergistically improve the corrosion resistance and conductivity of the magnesium alloy through different mechanisms. The micro-arc oxidation film layer provides a primary mechanical and chemical barrier, while the conductive film layer further improves the overall anti-corrosion performance of the system and gives the material a conductive function. The combination of the two enables the magnesium alloy to still maintain excellent protective performance and necessary electrical properties under harsh environments.
[0024] The components in the conductive coating of the present invention are specially optimized for application on a micro-arc oxidation film layer on a magnesium alloy during selection and proportioning, ensuring good adhesion, compatibility and functional synergy between the conductive film layer and the micro-arc oxidation film layer, thereby improving the corrosion resistance and conductivity of the magnesium alloy while maximizing the performance and durability of the overall film layer.
[0025] In addition, after research, the present invention has found that the micro-arc oxidation film has good surface morphology and roughness, which provides a better adhesion base for the coating of the conductive coating, ensuring the stability and durability of the film during use; and, the conductive film is prepared on the surface of the micro-arc oxidation film by direct coating, without the need for conductive preparation, which adapts to the high insulation characteristics of the micro-arc oxidation film, and can achieve full coverage of the micro-arc oxidation film with the conductive coating, and obtain a composite film with a coherent appearance. In addition, the surface treatment method provided by the present invention can also selectively perform local coating on the surface of the micro-arc oxidation film. Combined with the high insulation characteristics of the micro-arc oxidation film, the uncoated area has insulation and the coated area has conductivity, thereby meeting the local conductivity requirements of magnesium alloy parts and can adapt to different application scenarios.
[0026] The surface treatment method of the present invention has a simple preparation process, few operation steps, safety and environmental protection, is suitable for large-sized magnesium alloy structural parts, is not limited to the size of the structural parts, and enhances industrial application. The magnesium alloy conductive corrosion-resistant layer prepared by the present invention can reduce the surface interface contact resistance of the bipolar plate and enhance the corrosion resistance. Compared with existing metal materials such as aluminum, nickel, titanium and stainless steel, it can greatly reduce the weight of the proton exchange membrane fuel cell. In addition, the conductive corrosion-resistant layer prepared by the present invention is also suitable for magnesium alloy structural parts for aerospace.
[0027] In a preferred embodiment, the S1 specifically comprises the following steps: S1.1. Grind the surface of the magnesium alloy until it is smooth and free of impurities, clean and dry it; S1.2, degreasing, pickling and alkali washing the surface of the magnesium alloy after the treatment in S1.1; S1.3, performing micro-arc oxidation surface treatment on the surface of the magnesium alloy treated in S1.2.
[0028] The oil, lipids and other organic pollutants on the surface of the substrate are removed by degreasing, the impurities, oxide film, rust, slight corrosion products, etc. on the surface of the substrate are removed by pickling, and the pickling residues on the surface are removed by alkali washing; through the pretreatment steps S1.1 and S1.2 before micro-arc oxidation treatment, it is ensured that the surface of the substrate is clean, activated, and has a good surface state, so as to promote the uniform formation and firm adhesion of the oxide film during the micro-arc oxidation process and improve the quality of the micro-arc oxidation film layer.
[0029] In a preferred embodiment, the sandpaper used in the grinding process of S1.1 is SiC sandpaper with meshes of 180-1500, and the grinding is performed alternately in two vertical directions; the cleaning process includes cleaning with anhydrous ethanol and deionized water in sequence.
[0030] In a specific embodiment, the cleaning process first uses anhydrous ethanol for ultrasonic cleaning, and then rinses with deionized water; optionally, the time for using anhydrous ethanol for ultrasonic cleaning is 3 minutes to 15 minutes.
[0031] In a preferred embodiment, in the degreasing process of S1.2, the degreasing solution used for degreasing is a mixed solution including 2g / L-50g / L sodium hydroxide, 0g / L-2g / L sodium silicate, 1g / L-10g / L sodium carbonate, and 0g / L-30g / L sodium phosphate; optionally, the degreasing temperature is 40°C-80°C; optionally, the degreasing temperature is maintained by water bath heating; optionally, the degreasing time is 2min-10min.
[0032] In a preferred embodiment, in the pickling process of S1.2, the pickling solution used for pickling is a mixed solution including 5g / L-100g / L organic acid and 0g / L-50g / L sodium nitrate; wherein the organic acid is selected from at least one of glacial acetic acid, oxalic acid, citric acid, and tartaric acid; more preferably, the organic acid is selected from glacial acetic acid or oxalic acid; optionally, the pickling temperature is 30°C-50°C; optionally, the pickling temperature is maintained by water bath heating; optionally, the pickling time is 40s-60s.
[0033] In a preferred embodiment, in the alkali washing process of S1.2, the alkali washing solution used for alkali washing is a mixed solution including 5g / L-20g / L sodium hydroxide, 0g / L-10g / L sodium tripolyphosphate and 0g / L-10g / L sodium dodecyl sulfate; optionally, the alkali washing temperature is 50°C-70°C; optionally, the alkali washing temperature is maintained by water bath heating; optionally, the alkali washing time is 40s-60s.
[0034] In a preferred embodiment, the electrolyte for micro-arc oxidation surface treatment in S1.3 is a mixed solution including 5g / L-40g / L sodium silicate, 5g / L-50g / L sodium hydroxide, 0g / L-10g / L potassium fluoride, 0g / L-30g / L sodium tetraborate and 0g / L-40g / L sodium citrate; preferably, the temperature is kept below 40°C during the micro-arc oxidation surface treatment, the micro-arc oxidation time is 10min-30min, the constant voltage mode is adopted, the frequency is 600Hz-1000Hz, and the forward duty cycle is 12%-20%; preferably, after the micro-arc oxidation surface treatment, the magnesium alloy sample is cleaned and dried. Optionally, it is cleaned with anhydrous ethanol and deionized water in turn, dried with hot air, and then placed in a vacuum drying oven for drying at 30°C-60°C.
[0035] In a preferred embodiment, the conductive coating in S2 includes a conductive high molecular polymer, and the specific operating steps of S2 include: adding a binder to the conductive high molecular polymer and grinding until mixed evenly, adding a first organic solvent to mix and disperse to obtain a coating; preferably, the conductive high molecular polymer and the binder are dispersed in the first organic solvent by stirring and / or ultrasound; optionally, the above-mentioned dispersion is performed by ultrasound; preferably, the ultrasound time is 3h-30h, and more preferably, the ultrasound time is 15h-25h.
[0036] In another preferred embodiment, the conductive coating in S2 includes a conductive high molecular polymer, and the specific operation steps of S2 include: first dissolving the binder in a portion of the first organic solvent, then adding the conductive high molecular polymer and another portion of the first organic solvent, mixing and dispersing to obtain the coating. Preferably, in the specific operation of S2, at least 90% of the conductive high molecular polymer is dissolved in the first organic solvent; more preferably, at least 95% of the conductive high molecular polymer is dissolved in the organic solvent; more preferably, 96%, 97%, 98% or 99% of the conductive high molecular polymer is dissolved in the first organic solvent.
[0037] In a preferred embodiment, the conductive polymer is selected from at least one of polyaniline, polypyrrole and polythiophene. The micro-arc oxidation film has a certain chemical inertness, and conductive polymers such as polyaniline and polypyrrole are selected. They have good interface affinity and appropriate polar functional groups. These functional groups can form hydrogen bonds or van der Waals forces with oxides on the surface of the micro-arc oxidation film, thereby improving the adhesion of the film. These conductive polymers can also form a uniform protective film on the micro-arc oxidation film, further passivating the surface of the micro-arc oxidation film and reducing the occurrence of electrochemical corrosion.
[0038] In a specific embodiment, the conductive high molecular polymer is polyaniline; polyaniline has corrosion inhibition behavior and anion exchange properties, and can protect the underlying magnesium alloy substrate while being able to undergo anion exchange with chloride ions in the corrosive environment, thereby inhibiting the penetration of corrosive anions; at the same time, a binder is added to enhance the bonding strength between the polyaniline film layer and the magnesium alloy and to bond the polyaniline particles. Preferably, nano-oxides are added as corrosion inhibitors to further improve the corrosion resistance of the coating.
[0039] In a preferred embodiment, the conductive high molecular polymer is polypyrrole. Polypyrrole is conductive, and the polypyrrole film layer formed on the micro-arc oxidation film layer can provide an additional conductive path. At the same time, polypyrrole can form a uniform and dense film layer, which effectively blocks the contact between the corrosive medium and the magnesium alloy substrate, thereby providing good chemical stability and corrosion resistance, and due to its conductivity, polypyrrole can also promote the passivation of the metal surface, forming a protective oxide film, further improving the corrosion resistance. In addition, the interaction between polypyrrole and the micro-arc oxidation film layer can enhance the adhesion between the two, thereby improving the overall stability and durability of the composite film layer, and polypyrrole has good stability in the air, which means that the composite film layer can maintain its performance under different environmental conditions and is not prone to degradation or performance degradation.
[0040] In a preferred embodiment, the conductive polymer is polythiophene. Polythiophene itself is a conductive material, and the polythiophene film layer formed on the micro-arc oxidation film layer can provide an additional conductive path; and the introduction of polythiophene can improve the chemical stability of the composite film layer, thereby enhancing the protection of the magnesium alloy and preventing the corrosion of the corrosive medium. Since polythiophene has good chemical stability, it can act as a barrier to slow down the corrosion of the corrosive medium on the magnesium alloy substrate. In addition, the interaction between thiophene and the micro-arc oxidation film layer can enhance the adhesion between the two, thereby improving the overall stability and durability of the composite film layer.
[0041] In a preferred embodiment, the median particle size of the conductive polymer is in the range of 100nm-500nm. Conductive polymer particles with a median particle size in the range of 100nm-500nm are more likely to form a uniform film layer on the surface of the magnesium alloy, and the nanometer-scale particle size can better fill the surface micropores and irregular structures, thereby improving the density and uniformity of the film layer. This dense and uniform conductive film layer adheres more firmly to the micro-arc oxidation film layer, reducing the possibility of peeling of the conductive film layer; if the particle size is too large (>500nm), the particles may be difficult to form a uniform and dense film layer on the surface, resulting in uneven film layer and increased porosity, thereby reducing the adhesion and protective performance of the film layer; and too small a particle size (<100nm) may cause particle agglomeration, affecting the uniformity and structural integrity of the film layer. In the range of 100nm-500nm, conductive polymer particles can form an effective conductive network to improve the conductivity of the film layer. This conductive network has a good effect on electromagnetic shielding, corrosion protection and other electrical properties. Smaller particle size is conducive to improving the conductivity of the film layer and avoiding the "short circuit" phenomenon in the conductive path; too large particle size may reduce the contact area between particles, thereby reducing the overall conductivity; while too small particle size may cause the conductive network to be discontinuous, thereby reducing the conductive performance of the film layer. The film layer with a particle size in the range of 100nm-500nm is not only dense in structure, but also can provide good mechanical strength while maintaining a certain flexibility. Such a conductive film layer is not easy to crack or break when dealing with external mechanical stress; particles with too large particle size may make the film layer fragile and prone to cracking or peeling; while particles with too small particle size may cause the film layer to be thin and not strong enough, affecting its ability to resist mechanical damage. Therefore, within the particle size range of 100nm-500nm, the conductive film layer can achieve a good balance in terms of uniformity, conductivity, mechanical properties and controllability of the preparation process. However, exceeding this range will bring about problems such as poor film uniformity, low conductivity, poor mechanical properties and difficult to control the preparation process.
[0042] In a preferred embodiment, the mass ratio of the conductive polymer to the binder is 1:(0.1-0.3), for example, the mass ratio of the conductive polymer to the binder is any value among 1:0.1, 1:0.13, 1:0.15, 1:0.18, 1:0.20, 1:0.22, 1:0.25, 1:0.28, 1:0.3 or any value in the middle value formed by any two points. The function of the binder is to fix the conductive polymer on the surface of the micro-arc oxidation film layer and fill the tiny gaps that may be generated in the conductive film layer, thereby improving the overall adhesion of the film layer. The right amount of binder can ensure that the film layer is evenly and firmly attached to the surface of the micro-arc oxidation film layer to prevent peeling or falling off. In the range of mass ratio 1: (0.1-0.3), the amount of binder can effectively enhance the adhesion between the conductive film layer and the micro-arc oxidation film layer; if the binder is too much (greater than 0.3), it will occupy too much volume in the conductive film layer, resulting in a decrease in the concentration of the conductive polymer, thereby reducing the overall conductivity and conductivity of the conductive film layer. Excessive binder will also lead to poor mechanical properties and elasticity of the conductive film layer, making the conductive film layer more brittle, and also increase unnecessary costs. More preferably, the mass ratio of the conductive polymer to the binder is 1: (0.15-0.25).
[0043] In a preferred embodiment, the binder is selected from at least one of polyvinylidene fluoride, polyacrylonitrile, polyethersulfone, vinyl acetate copolymer, and polyethylene terephthalate; more preferably, the binder is selected from polyvinylidene fluoride or polyacrylonitrile. Polyvinylidene fluoride (PVDF) has excellent chemical resistance and heat resistance, can maintain the stability of the film layer in harsh environments, and the high mechanical strength and excellent adhesion of PVDF make the prepared conductive film layer more durable. Polyacrylonitrile (PAN) has high mechanical strength and good thermal stability, can enhance the toughness of the film layer, and can be well combined with conductive polymers to improve the overall mechanical properties of the conductive film layer. Polyethersulfone (PES) has excellent heat resistance and chemical corrosion resistance, and is suitable for applications in high temperature or chemical environments. Its stability and high glass transition temperature can improve the durability and stability of the conductive film layer. Vinyl acetate copolymer (EVA) has good flexibility and adhesion, can increase the mechanical flexibility of the conductive film layer, and is conducive to the uniform distribution of the conductive film layer. Its low glass transition temperature makes the conductive film layer have good toughness. The chemical resistance and mechanical strength of polyethylene terephthalate (PET) make the conductive film layer stable in a variety of environments, and can enhance the mechanical strength and impact resistance of the conductive film layer. The surface of the micro-arc oxidation film layer is relatively hard and has microscopic roughness. Adhesives such as polyvinylidene fluoride (PVDF) and polyacrylonitrile (PAN) can form a film layer with strong adhesion on this surface. The molecular structure and chemical properties of these adhesives are suitable for combining with the chemical groups on the surface of the oxide film layer to provide strong mechanical adhesion. In addition, adhesives with appropriate thermal expansion coefficients are selected to match the physical properties of the micro-arc oxidation film layer to reduce the risk of peeling or cracking of the composite film layer under temperature changes.
[0044] In a preferred embodiment, the first organic solvent is selected from at least one of xylene, N-methylpyrrolidone, tetrahydrofuran, dimethylformamide, and dichlorobenzene; for example, the first organic solvent is N-methylpyrrolidone. Xylene has good solubility and volatility, can effectively dissolve a variety of polymer materials, and help form a uniform coating solution. Due to its moderate volatilization rate, xylene can evaporate quickly after the conductive film layer is coated, ensuring that the film layer dries quickly while reducing defects in the conductive film layer. N-methylpyrrolidone (NMP) is a polar solvent that can well dissolve conductive polymers such as polypyrrole and polyaniline, as well as many binders (such as PVDF). The polarity and high boiling point of NMP make it suitable for coating formulations that require good solubility and long-term operation, which can ensure that the conductive film layer can be evenly distributed after coating. Tetrahydrofuran (THF) is a low-boiling polar solvent that can dissolve and evaporate quickly. It is suitable for film applications that require fast drying. THF has good solubility and can help form a uniform coating system and improve the smoothness and uniformity of the conductive film. Dimethylformamide (DMF) is a highly polar solvent with a high boiling point. It can dissolve conductive polymers and binders well. It is particularly suitable for coating formulations that need to maintain coating stability for a long time. Since DMF can dissolve a variety of polymer materials, it can ensure the uniformity and stability of the conductive film. Dichlorobenzene has good solubility and a high boiling point. It can dissolve some difficult-to-dissolve polymer materials, help improve the fluidity of the coating and the uniformity of the film, and is suitable for thicker film applications. Its volatilization rate is moderate, ensuring that the conductive film has sufficient leveling time during the coating process. These organic solvents can effectively dissolve conductive polymers and binders, ensuring that the various components in the coating can be fully mixed to form a uniform and stable coating system; high boiling point solvents such as NMP and DMF help to extend the operating time of the coating and are suitable for coating systems that require longer construction times; different organic solvents have different physical and chemical properties. Choosing a suitable organic solvent can control the drying speed of the coating, ensure the uniformity and smoothness of the conductive film layer, help form a dense and uniform conductive film layer, improve the mechanical strength, adhesion and conductivity of the film layer, adapt to the surface characteristics of the micro-arc oxidation film layer, ensure that the film layer can be evenly covered and firmly adhered, and avoid the appearance of bubbles or shrinkage holes in the film layer.
[0045] In a preferred embodiment, to ensure the performance, operability and film quality of the coating, 3mL-10mL of the first organic solvent is added for every 1g of the conductive polymer. Within the range of 3mL-10mL of the solvent amount, the conductive polymer can be fully dissolved or dispersed in the organic solvent to form a uniform solution or dispersion, which helps to ensure that the conductive coating remains uniform during the construction process and avoids local uneven concentration or particle agglomeration; the amount of solvent within this range can adjust the viscosity of the conductive coating so that it has good fluidity and can form a uniform and continuous film layer during the coating process. The appropriate viscosity helps to control the film thickness and ensure that the coating is well attached to the surface of the micro-arc oxidation film layer; and within this range, the coating has good operability and will not be too viscous or diluted. The moderate viscosity and fluidity make the coating easy to apply, suitable for different coating methods (such as brushing, dipping and pulling, etc.), and reduce the difficulty of construction; the amount of solvent of 3mL-10mL allows the film layer to dry evenly after application to form a dense film layer structure, and the appropriate solvent evaporation rate helps the film layer to level and reduce surface defects such as pinholes or bubbles, thereby improving the overall quality and conductive performance of the film layer. If the amount of solvent is too little, the conductive polymer may not be fully dissolved or dispersed, causing the coating to be too viscous or form an uneven suspension. This will affect the fluidity and applicability of the coating, resulting in uneven film thickness, incomplete film or rough surface; in addition, insufficient solvent may cause the polymer in the coating to coagulate prematurely, forming agglomeration, affecting the conductivity and film quality. If the amount of solvent is too much, the conductive coating will become too thin, making it difficult to control the thickness of the film during coating, and may form a too thin film, affecting the mechanical strength and conductive properties of the film; too much solvent may also cause the conductive coating to fail to effectively adhere to the surface of the micro-arc oxidation film, increasing the risk of sagging or dripping; in addition, too much solvent will prolong the drying time, which may cause the solvent to be retained in the film, forming pinholes or bubbles, reducing the density and durability of the film. The range of 3mL-10mL of solvent provides a good balance, which can ensure the solubility and dispersibility of the conductive polymer in the coating, ensure that the coating has moderate viscosity, good operability, and can form a uniform and dense film layer. Exceeding this range may lead to a decrease in coating performance, affecting the quality and use effect of the film layer. More preferably, 4mL-8mL of the first organic solvent is added for every 1g of the conductive polymer; most preferably, 5mL of the first organic solvent is added for every 1g of the conductive polymer.
[0046] In a preferred embodiment, the conductive coating in S2 also includes a corrosion inhibitor, and the corrosion resistance of the conductive coating is improved by adding the corrosion inhibitor. The specific operation steps are: adding a binder and a corrosion inhibitor to the conductive polymer, grinding until the mixture is uniform, adding a first organic solvent, mixing and dispersing, and obtaining the conductive coating.
[0047] In another preferred embodiment, the binder is first dissolved in a portion of the first organic solvent, and then the conductive polymer, the corrosion inhibitor and another portion of the first organic solvent are added, mixed and dispersed to obtain a conductive coating.
[0048] In a preferred embodiment, the corrosion inhibitor includes nano oxides, specifically, the nano oxides are selected from at least one of SiO2, ZnO, TiO2, TiN, and MnO2, for example, the nano oxides include SiO2 and TiO2. As corrosion inhibitors, the nano oxides give the conductive film layer better corrosion resistance, and the nano oxides can form a synergistic effect with the conductive polymer and the binder, further improving the barrier effect of the film layer against the corrosive medium.
[0049] Preferably, the nano-oxide is spherical, flaky, fibrous or irregular particles with a median particle size of 15nm-60nm. Spherical particles have a lower specific surface area and good fluidity, and can be evenly distributed in the coating. Particles of this shape can reduce the possibility of aggregation, form a uniform and dense film structure, and help improve the overall protective effect of the film; flaky particles can form a "brick wall" barrier structure in the film, improve the film's barrier effect on corrosive media, and can effectively extend the diffusion path of corrosive media in the conductive film, and cooperate with the inner micro-arc oxidation film to enhance the overall corrosion resistance of the magnesium alloy composite film. Fibrous particles can increase the mechanical strength and toughness of the film, help improve the crack resistance and wear resistance of the film, and can form a continuous three-dimensional network structure in the film to enhance the structural strength of the film. Irregular particles have a higher specific surface area, can provide a more effective barrier effect and stronger interface adhesion, can fill the micropores and defects in the film, and improve the density and anti-corrosion performance of the film. Nano oxides with a particle size of 15nm-60nm can effectively fill the tiny gaps in the film layer and increase the density of the film layer. Nano-scale particles can be more evenly dispersed in the conductive coating to form a more uniform film structure, thereby improving the film's anti-permeability performance. Within this particle size range, nano oxides have a larger specific surface area and can provide a more effective barrier effect, delaying the penetration of corrosive media. At the same time, nano particles can also form a good interface with other components in the coating (such as binders), further improving the film's anti-corrosion performance. Nano oxides can enhance the mechanical support inside the film layer, reduce the formation and expansion of cracks, and thus improve the mechanical strength and wear resistance of the film layer. However, too small a particle size will cause the particles to easily agglomerate and form large particle clusters, which will reduce the uniformity and density of the film layer. In addition, too small a particle size will increase the difficulty of manufacturing and dispersion, and the stability of the coating will be affected. However, a particle size that is too large will reduce the specific surface area of the nano-oxide, thereby reducing its barrier effect and anti-corrosion performance. Larger particles are also more difficult to disperse evenly in the coating, resulting in uneven film and increased surface roughness. In addition, a particle size that is too large will reduce the density of the film, increase the risk of penetration of corrosive media, and reduce the overall corrosion inhibition effect. Nano-oxides with a median particle size of 15nm-60nm combined with their shape characteristics can provide the best anti-corrosion, reinforcement and barrier effects in the film, ensuring the density and uniformity of the film.
[0050] Preferably, the amount of corrosion inhibitor added is 0.5%-3.0% of the sum of the mass of the conductive polymer and the binder, and more preferably, the amount of corrosion inhibitor added is 1.0%-2.0% of the sum of the mass of the conductive polymer and the binder, for example, any value among 0.8%, 1.0%, 1.2%, 1.4%, 1.6%, 1.8%, 2.0%, 2.5%, 2.8% or any value in the middle of any two points.
[0051] In a preferred embodiment, the conductive coating of S2 includes carbon nanotubes, which specifically includes the following steps: grinding the carbon nanotubes uniformly, adding a second organic solvent to mix and disperse, and obtaining the conductive coating.
[0052] Preferably, the carbon nanotube has a diameter of 20nm-40nm and a length of 1μm-2μm. Carbon nanotubes with a diameter in the range of 20nm-40nm are easier to disperse in organic solvents; and carbon nanotubes with a smaller diameter are conducive to forming a denser conductive network, thereby more effectively improving the conductivity of the film layer. In addition, carbon nanotubes with a smaller diameter have a higher current carrying capacity and can provide better conductivity. Carbon nanotubes with a diameter in the range of 20nm-40nm not only provide excellent conductivity, but also have good mechanical strength, which helps the composite film layer maintain integrity under stress and prevent cracking or falling off. Carbon nanotubes with a diameter that is too small have a larger specific surface area and are prone to agglomeration, resulting in difficulty in dispersion in the solvent, which may lead to uneven areas in the film layer, and overly thin carbon nanotubes are more likely to break under stress, which may reduce the overall mechanical properties of the composite film layer. The volume occupied by carbon nanotubes with too large diameter in the conductive coating increases, which may lead to a decrease in the density of the conductive network, thereby reducing the conductivity of the composite film layer. In addition, a larger diameter may increase the surface roughness of the film layer, affecting the uniformity and adhesion of the film layer, which may cause the film layer to be microscopically non-uniform and increase the risk of corrosion. Carbon nanotubes with a length of 1μm-2μm are long enough to cross the gaps in the conductive film layer to form a continuous conductive path, which helps to enhance the overall conductivity of the composite film layer. Especially when the thickness of the conductive film layer is large, longer carbon nanotubes can more easily form a conductive network in a three-dimensional structure; in addition, longer carbon nanotubes have better tensile strength and toughness, which can effectively enhance the mechanical properties of the composite film layer and improve its wear resistance and crack resistance. Carbon nanotubes with too short lengths are difficult to cross large gaps in the film layer, which may lead to discontinuity of the conductive network and reduce the overall conductivity. In addition, short carbon nanotubes cannot effectively improve the mechanical properties of the composite film layer, which may increase the brittleness of the composite film layer and make it easy to crack. However, carbon nanotubes that are too long tend to get tangled together, making it difficult to disperse. This agglomeration phenomenon can lead to uneven film layers, affecting their conductivity and protective properties. Too long carbon nanotubes can also increase the difficulty of coating preparation and coating processes, increasing process complexity and costs. Limiting the diameter of carbon nanotubes to 20nm-40nm and the length to 1μm-2μm can achieve a good balance in terms of conductivity, dispersion, and mechanical strength. Carbon nanotubes within this size range can form a uniform and stable conductive network in the film layer, while enhancing the mechanical properties of the composite film layer, so that the composite film layer has excellent conductivity and corrosion resistance on the magnesium alloy micro-arc oxidation film layer; carbon nanotubes beyond this range may lead to problems such as difficulty in dispersion, reduced conductivity, and uneven film layers, thereby affecting the overall performance of the composite film layer.
[0053] Preferably, the dispersion of the carbon nanotubes in the second organic solvent is performed by stirring and / or ultrasound; optionally, the dispersion is performed by ultrasound, preferably, the ultrasound time is 3h-30h, more preferably, the ultrasound time is 3h-25h.
[0054] Preferably, the second organic solvent is selected from one of N-methylpyrrolidone and dimethylformamide. N-methylpyrrolidone (NMP) is a highly polar organic solvent that can well disperse carbon nanotubes to prevent them from agglomerating, and NMP can fully wet the surface of carbon nanotubes to form a stable dispersion system; at the same time, NMP has a high boiling point and a slow volatility, allowing the conductive coating to have enough time to level during the coating process to form a uniform film layer and reduce surface defects. Dimethylformamide (DMF) can effectively disperse carbon nanotubes, and DMF has a low surface tension, which helps the coating to form a uniform film layer on the micro-arc oxidation film layer, reducing the risk of bubbles and uneven film layers; in addition, DMF can enhance the wettability of the conductive coating and the surface of the micro-arc oxidation film layer, and improve the adhesion of the film layer. These two organic solvents can significantly affect the quality and performance of the conductive film layer, ensure that the film layer is uniformly and stably attached to the magnesium alloy micro-arc oxidation film layer, and effectively give the magnesium alloy conductivity and corrosion resistance.
[0055] In a preferred embodiment, the coating method in S3 is spin coating, and the specific operation steps include: placing the magnesium alloy treated by S1 on the turntable of the coating machine, using a straw to absorb an appropriate amount of the conductive coating dispersed in S2 and dripping it into the middle of the magnesium alloy, and starting spin coating to prepare a film layer. After the spin coating is completed, the magnesium alloy is taken out and placed in a vacuum drying oven for low-temperature drying; during the spin coating, the spin coating temperature is 5°C-25°C, the rotation speed is 500r / min-1500r / min, and the acceleration is 300m / s 2 -600m / s 2, the spin coating time is 5s-20s. The spin coating method is to rotate the specimen at high speed so that the conductive coating is evenly distributed on the surface of the specimen under the action of centrifugal force. This method can form a film layer with uniform thickness on the surface of the magnesium alloy micro-arc oxidation film layer, and is particularly suitable for preparing a film with precise thickness control. The spin coating method accurately controls the thickness of the film layer by adjusting parameters such as the rotation speed, time and coating viscosity. It is very suitable for preparing application scenarios that require thin and uniform film layers, especially for composite film layers with high requirements for conductivity and corrosion resistance. The operation time is short and the film layer can be prepared within a few seconds to tens of seconds. It is suitable for efficient mass production. Since the coating is evenly distributed to the surface by centrifugal force during the spin coating process, the excess coating will be thrown out and collected, thereby reducing material waste. For expensive conductive materials, the spin coating method is particularly advantageous. In the embodiment of the present invention, the spin coating temperature is in the range of 5°C-25°C, which helps to control the viscosity and surface tension of the conductive coating, thereby affecting the uniformity of the film layer. The lower temperature helps to slow down the evaporation rate of the solvent, so that the conductive coating has more time to flow and form a uniform film during the coating process. The embodiment of the present invention flexibly controls the thickness of the film layer by setting the rotation speed. A lower rotation speed is suitable for a thicker film layer, while a higher rotation speed helps to form a thinner and more uniform film layer. By adjusting the rotation speed, adaptation to different conductive coating viscosities and surface properties can be achieved. Appropriate acceleration can ensure that the conductive coating spreads evenly over the entire surface without forming ripples or defects; a higher acceleration helps to quickly form a uniform film layer, while a lower acceleration can control the fluidity of the conductive coating and prevent the thickness of the conductive coating at the edge from increasing. The setting of the spin coating time allows for full adjustment of the distribution of the conductive coating on the workpiece surface. A longer time is suitable for the formation of a thicker film layer, while a shorter time helps to quickly form a thin film to avoid excessive solvent volatilization affecting the uniformity of the film layer. The embodiment of the present invention adopts a spin coating method, which has significant advantages such as forming a uniform thin film, accurately controlling the film thickness, efficient production, and reducing material waste. Through reasonable process parameter settings, including spin coating temperature, rotation speed, acceleration and time, the uniformity, thickness and surface quality of the film layer can be further optimized, thereby improving the conductivity and corrosion resistance of the film layer. The method of this embodiment is suitable for preparing a film layer with high performance requirements, and can maximize the process efficiency when processing smaller-sized magnesium alloy samples.
[0056] In a preferred embodiment, the coating method in S3 is immersion pulling, and the specific operating steps include: hanging the magnesium alloy treated by S1 on an immersion pulling coating machine, completely immersing it in the conductive coating dispersed in S2, then pulling it out, waiting for natural surface drying, taking out the magnesium alloy and placing it in a vacuum drying oven for low-temperature drying; during immersion pulling, the magnesium alloy sample needs to keep the bottom of the sample tangent to the liquid surface, the rising speed and the descending speed are 500μm / s-1500μm / s, the immersion time is 60s-300s, the number of coating times is 1-2 times, and the pulling height depends on the sample height and needs to exceed the sample height. For example, if the height of the magnesium alloy sample after hanging is 20mm, the pulling height is set to 22mm. The immersion and pulling method can ensure that the coating forms a uniform film layer on the surface of the magnesium alloy. Since the workpiece is slowly immersed and pulled, the conductive coating can evenly cover the entire surface under the combined action of gravity and surface tension, avoiding the problem of uneven film thickness; the immersion and pulling method is particularly suitable for workpieces with complex shapes. Since the workpiece is completely immersed in the conductive coating, even complex geometric structures or difficult-to-reach areas can be evenly coated. The embodiment of the present invention can accurately control the thickness of the film layer by adjusting the pulling speed and immersion time; and the film layer is formed by the natural flow of the liquid, reducing common problems such as bubbles and flow marks, resulting in fewer surface defects and good film quality. In the embodiment of the present invention, during immersion, ensuring that the bottom of the magnesium alloy sample is tangent to the liquid surface helps to avoid excessive paint accumulation at the bottom of the sample and ensure uniform film thickness. The uniformity of the film thickness directly affects the final conductivity and corrosion resistance. The embodiment of the present invention controls the rising speed and the falling speed to ensure uniform coating coverage while reducing the time the liquid adheres to the surface of the sample. Too fast rising speed and falling speed may cause the film layer to be too thin, while too slow speed may cause conductive coating accumulation and uneven film layer. This speed range can effectively control the film thickness and avoid the generation of defects. In the embodiment of the present invention, the setting of the immersion time allows the conductive coating to fully infiltrate the surface of the micro-arc oxidation film layer and enter the tiny surface pores or cracks to form a better coverage effect. The moderate immersion time ensures that the conductive coating can fully combine with the micro-arc oxidation film layer to improve the adhesion and quality of the composite film layer. The embodiment of the present invention can further improve the uniformity and thickness of the film layer through multiple coatings. A layer of coating may have microscopic defects in certain areas. The second layer of coating can fill these defects and enhance the overall performance of the film layer. After two coatings, the corrosion resistance and conductivity of the film layer are significantly improved. The embodiment of the present invention is subjected to natural surface drying after pulling, so that the solvent can be partially volatilized to form a preliminary film layer structure, and then low-temperature drying is performed in a vacuum drying oven to further remove the residual solvent, while avoiding thermal stress of the film layer caused by high temperature, thereby ensuring the uniformity and adhesion of the film layer.The embodiment of the present invention can accurately control the thickness and quality of the film layer through reasonably designed process parameters, including descent speed, immersion time and pulling height, thereby maximizing the performance of the composite film layer while improving the conductivity and corrosion resistance of the composite film layer.
[0057] In a preferred embodiment, the coating method in S3 is brush coating, and the specific operation steps include: placing the magnesium alloy treated by S1 flat on the table, using a small brush to dip the conductive coating dispersed in S2, and brushing it evenly and evenly on the magnesium alloy until the conductive coating completely covers the micro-arc oxidation film layer, brushing 1-3 times, then pulling it out, waiting for natural surface drying, taking out the magnesium alloy and placing it in a vacuum drying oven for low-temperature drying. The brush coating method allows local precise control of the coating area. For parts with complex shapes or special needs, brushing can be used to ensure that each area is evenly coated. There are not many restrictions on the shape, size and coating area of the workpiece, and it is suitable for coating magnesium alloy parts of different shapes and sizes. This is particularly important when processing small or complex geometric workpieces. The brush coating method can achieve local coating of conductive coatings, thereby achieving local conductivity of the magnesium alloy composite film layer; and the brush coating method usually requires low equipment and material costs, simple operation, and does not require special coating equipment, which is suitable for coating needs in small batches or laboratory environments. The brushing method adjusts the coating thickness and uniformity according to actual needs, and the final effect of the film layer can be adjusted by controlling the strength and direction of the brushing. In the embodiment of the present invention, the use of a small brush can better control the amount of paint and the accuracy of the coating, and can more evenly apply the conductive paint to complex surfaces and small gaps to ensure uniform coverage of all areas; multiple brushing can ensure the uniformity and thickness of the film layer, and the drying time interval of each brushing can allow the paint to fully penetrate and adhere to the surface, thereby improving the overall quality and performance of the film layer; the number of brushing can be adjusted as needed to optimize the conductivity and corrosion resistance of the film layer. In the embodiment of the present invention, the natural surface drying process allows the paint to dry evenly without external interference, reducing film defects (such as cracking or blistering) caused by rapid drying, and natural surface drying also helps to improve the adhesion of the film layer; low-temperature vacuum drying helps to remove residual solvents and avoid thermal stress caused by high temperature on the film layer, thereby maintaining the integrity and performance of the film layer. Low-temperature drying under a vacuum environment can prevent bubbles and defects in the film layer and ensure the uniformity and corrosion resistance of the film layer. The brush coating method provides a high degree of operational flexibility, precise control capability and low cost when applying conductive coatings on magnesium alloy micro-arc oxidation films. Through reasonable process design, including laying the workpiece flat, using a small brush, controlling the number of brushing passes, and adopting natural surface drying and vacuum low-temperature drying, the uniformity, adhesion and performance of the film layer can be further optimized, thereby achieving excellent conductivity and corrosion resistance.
[0058] An embodiment of the present invention provides a magnesium alloy part, which is prepared by the surface treatment method of the magnesium alloy.
[0059] An embodiment of the present invention provides an application of a magnesium alloy part in a proton exchange membrane fuel cell, wherein the magnesium alloy part is used as a magnesium alloy bipolar plate of the proton exchange membrane fuel cell.
[0060] Example 1 This embodiment provides a surface treatment method for a magnesium alloy, comprising the following steps: S1. Preparation of micro-arc oxidation film on magnesium alloy surface: S1.1. AZ31 magnesium alloy was used as the substrate, and the surface was polished step by step with 180 mesh, 400 mesh, 800 mesh, 1200 mesh, and 1500 mesh SiC sandpaper until the surface was smooth and flat. After polishing, anhydrous ethanol was ultrasonicated for 5 minutes, and then the surface was washed with deionized water and dried; S1.2, degreasing, pickling and alkali washing the surface of the magnesium alloy after the treatment in S1.1: Degreasing: Place the mechanically polished magnesium alloy sample in a mixed solution of 30 g / L sodium hydroxide, 5 g / L sodium carbonate and 30 g / L sodium phosphate, completely immerse it, and soak it at 60°C for 10 minutes. Take it out and rinse it with deionized water; Pickling: Place the degreased magnesium alloy sample in a mixed solution of 10 g / L oxalic acid and 5 g / L tartaric acid, immerse it completely, soak it at 40 °C for 40 seconds, take it out and rinse it with deionized water; Alkaline washing: the pickled magnesium alloy sample was placed in a mixed solution of 10 g / L sodium hydroxide, 5 g / L sodium tripolyphosphate and 0.5 g / L sodium dodecyl sulfate, immersed at 60 °C for 40 s, and then taken out and rinsed with deionized water; S1.3, micro-arc oxidation surface treatment: the pretreated magnesium alloy sample is connected to the anode of the micro-arc oxidation power supply, and completely immersed in the micro-arc oxidation electrolyte. The electrolyte is a mixed solution composed of 10g / L sodium silicate, 50g / L sodium hydroxide and 5g / L potassium fluoride; the constant voltage mode is adopted, the frequency is set to 600Hz, and the forward duty cycle is 12%; the electrolyte temperature is set to 20℃, the micro-arc oxidation time is 20min, and then the sample is taken out, rinsed with deionized water and placed in a vacuum drying oven at 50℃ for 10min to prepare a magnesium alloy with a micro-arc oxidation film on the surface; S2. Prepare conductive coating: weigh 0.6 g polyaniline and 0.1 g polyvinylidene fluoride, first grind in a mortar for 20 min until the solid coating is physically mixed evenly and the white particles of polyvinylidene fluoride disappear, then drop 3 ml N-methylpyrrolidone, stir until the mixture is evenly mixed, and ultrasonically disperse for 3.5 h to obtain conductive coating 1; S3. Spin coating to prepare composite film layer: set the spin coating temperature to 20°C, the rotation speed to 1000r / min, and the acceleration to 500m / s 2 , the spin coating time is 10s. Take 1ml of conductive coating 1 and drop it in the middle of the magnesium alloy micro-arc oxidation film layer, start spin coating, and put it into a vacuum drying oven after spin coating to remove a small amount of bubbles on the surface and dry it.
[0061] As attached Figure 2 As shown in (a), the magnesium alloy micro-arc oxidation film prepared in this embodiment is white and has a uniform and dense appearance. Figure 2 As shown in (b), the magnesium alloy micro-arc oxidation-polyaniline composite film is black, completely covering the white micro-arc oxidation film.
[0062] Attached Figure 3 The dynamic position planning curve diagram of the magnesium alloy micro-arc oxidation film layer and the magnesium alloy micro-arc oxidation-polyaniline composite film layer in this embodiment is shown in the attached figure. Figure 3 Combined with Table 1, it can be seen that compared with the magnesium alloy substrate, the self-corrosion potential of the magnesium alloy micro-arc film layer prepared in this embodiment is positively shifted, and the self-corrosion current density is reduced, indicating that the micro-arc oxidation film layer can improve the corrosion resistance of the magnesium alloy substrate, while the self-corrosion potential of the magnesium alloy micro-arc oxidation-polyaniline composite film layer is positively shifted compared to the micro-arc oxidation film layer, and the self-corrosion current density is increased. At this time, the corrosion resistance is reduced, but it is still better than the substrate, and the conductivity is enhanced.
[0063] Table 1 Potentiodynamic polarization curve fitting data of magnesium alloy (AZ31), magnesium alloy micro-arc oxidation film (MAO) and magnesium alloy micro-arc oxidation-polyaniline composite film (MAO-PANI)
[0064] Example 2 This embodiment provides a surface treatment method for a magnesium alloy, comprising the following steps: S1. Preparing a micro-arc oxidation film on the surface of a magnesium alloy: the same as S1 in Example 1; S2. Preparation of conductive coating: 3 g of carbon nanotubes (diameter of 20 nm-40 nm, length of 1 μm-2 μm) were weighed and ground in a mortar for 20 min to make the particles finer. Then, 10 ml of NMP was added to the carbon nanotubes, stirred until the mixture was uniform, and ultrasonically dispersed for 10 h to obtain conductive coating 2. S3. Prepare the composite film layer by brushing: Take a small brush and dip it into the conductive coating 2, start brushing along one direction, apply it evenly, apply it 2 times, until the conductive coating 2 completely covers the surface of the magnesium alloy micro-arc oxidation film layer, then put it into a vacuum drying oven to remove a small amount of bubbles on the surface and dry it.
[0065] As attached Figure 4As shown in (a), the magnesium alloy micro-arc oxidation film prepared in this embodiment is white and has a uniform and dense appearance. Figure 4 As shown in (b), the magnesium alloy micro-arc oxidation-carbon nanotube composite film is black, completely covering the white micro-arc oxidation film.
[0066] As shown in Table 2, the resistance values of magnesium alloy, magnesium alloy micro-arc oxidation film and magnesium alloy micro-arc oxidation-carbon nanotube composite film were tested. It can be seen from the table that micro-arc oxidation treatment of magnesium alloy greatly increases the resistance value of the substrate, which further illustrates the protectiveness of the micro-arc oxidation film on the substrate. The resistance value of the magnesium alloy micro-arc oxidation-carbon nanotube composite film is significantly reduced, and the conductivity of the film is enhanced.
[0067] Table 2 Resistance values of magnesium alloy (AZ31), magnesium alloy micro-arc oxidation film (MAO) and magnesium alloy micro-arc oxidation-carbon nanotube composite film (MAO-CNT)
[0068] Example 3 This embodiment provides a surface treatment method for a magnesium alloy, comprising the following steps: S1. Preparing a micro-arc oxidation film on the surface of a magnesium alloy: the same as S1 in Example 1; S2. Prepare conductive coating: weigh 0.5 g polyaniline and 0.1 g polyvinylidene fluoride, first grind in a mortar for 20 min until the solid coating is physically mixed evenly and the white polyvinylidene fluoride particles are invisible to the naked eye, then add 2.5 ml N-methylpyrrolidone, stir until the mixture is evenly mixed, and ultrasonically disperse for 10 h to obtain conductive coating 3; S3. Spin coating to prepare composite film layer: set the spin coating temperature to 20°C, the rotation speed to 800r / min, and the acceleration to 500m / s 2 , the spin coating time is 15s; take 1ml of conductive coating and add 3 drops in the middle of the magnesium alloy micro-arc oxidation film layer, start spin coating, and put it into a vacuum drying oven after spin coating to remove a small amount of bubbles on the surface and dry it.
[0069] Example 4 This embodiment provides a surface treatment method for a magnesium alloy, comprising the following steps: S1. Preparing a micro-arc oxidation film on the surface of a magnesium alloy: the same as S1 in Example 1; S2. Prepare a conductive coating: weigh 0.6 g of polyaniline and 0.1 g of polyvinylidene fluoride, first grind them in a mortar for 20 min until the solid coating is physically mixed evenly and no white polyvinylidene fluoride particles are visible to the naked eye, then add 3 ml of xylene, stir until the mixture is evenly mixed, and perform ultrasonic dispersion for 3.5 h to obtain a conductive coating 4; S3. Spin coating to prepare composite film layer: set the spin coating temperature to 20°C, the rotation speed to 1000r / min, and the acceleration to 500m / s 2 , the spin coating time is 15s; take 1ml of conductive coating and add 4 drops in the middle of the magnesium alloy micro-arc oxidation film layer, start spin coating, and put it into a vacuum drying oven after spin coating to remove a small amount of bubbles on the surface and dry it.
[0070] Example 5 This embodiment provides a surface treatment method for a magnesium alloy, comprising the following steps: S1. Preparing a micro-arc oxidation film on the surface of a magnesium alloy: the same as S1 in Example 1; S2. Prepare conductive coating: weigh 0.6g polyaniline and 0.1g polyvinylidene fluoride, add spherical TiO2 (median particle size is 30nm) with a total weight of 1.5% of the total weight of polyaniline and polyvinylidene fluoride, first grind in a mortar for 20min until the solid coating is physically mixed evenly and the white particles of polyvinylidene fluoride are invisible to the naked eye, then add 3ml N-methylpyrrolidone, stir until the mixture is evenly mixed, and ultrasonically disperse for 3.5h to obtain conductive coating 5; S3. Spin coating to prepare composite film layer: set the spin coating temperature to 20°C, the rotation speed to 1000r / min, and the acceleration to 500m / s 2 , the spin coating time is 10s; take 1ml of conductive coating and add 5 drops in the middle of the magnesium alloy micro-arc oxidation film layer, start spin coating, and put it into a vacuum drying oven after spin coating to remove a small amount of bubbles on the surface and dry it.
[0071] Application Example 1 In Example 1, Figure 3 The bipolar plate dynamic potential polarization curve test shown in the figure was performed using a Wuhan Corrtest CS350 electrochemical workstation for potential scanning tests, all of which used a three-electrode system. The magnesium alloy sample with a composite film layer prepared in Example 1 was used as the working electrode, the Ag / AgCl electrode was used as the reference electrode, the platinum mesh was used as the auxiliary electrode, the corrosive medium was a 3.5wt.% NaCl solution, and the test area was 1cm 2 The sample was immersed in the corrosive medium until the open circuit potential was stable, and then a dynamic potential scanning test was performed. The dynamic potential scanning interval was (-0.5) V-0.5 V relative to the open circuit potential, and the scanning rate was 1 mV / s. The results showed that the self-corrosion current density of the AZ31 magnesium alloy sample was 2.404×10 - Ω / cm 2 , the self-corrosion potential is -1.59V, and the polarization resistance is 0.21×10 7 Ω / cm 2 The self-corrosion current density of the MAO sample is 4.16×10 -7 Ω / cm 2, the self-corrosion potential is -1.35V, and the polarization resistance is 5.63×10 7 Ω / cm 2 The self-corrosion current density of MAO-PANI sample is 2.70×10 -6 Ω / cm 2 , the self-corrosion potential is -1.48V, and the polarization resistance is 0.66×10 7 Ω / cm 2 .
[0072] In summary, the micro-arc oxygen layer prepared by the method described in the embodiment of the present invention has good bonding with the magnesium alloy and excellent corrosion resistance. After coating the conductive film layer, the corrosion resistance will decrease slightly, but the conductivity will be enhanced. The method for preparing the composite film layer provided in the embodiment of the present invention has simple operating steps, easy to control reaction conditions, and ingenious design ideas.
[0073] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0074] The above-mentioned embodiments only express several implementation modes of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention. It should be pointed out that, for a person of ordinary skill in the art, several modifications and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the attached claims.
[0075] The contents not described in detail in this specification belong to the prior art known to professional and technical personnel in this field.
Claims
1. A surface treatment method for a magnesium alloy, characterized in that: The following steps are involved: S1. Preparing a micro-arc oxidation film on the surface of a magnesium alloy; S2, preparing a conductive coating; the conductive coating comprises a conductive polymer or carbon nanotubes; S3, coating the conductive coating obtained in S2 on the surface of the micro-arc oxidation film layer obtained in S1 to obtain a composite film layer.
2. The surface treatment method of magnesium alloy according to claim 1, characterized in that: The S1 comprises the following steps: S1.
1. Grind the surface of the magnesium alloy until it is smooth, clean and dry; S1.2, degreasing, pickling and alkali washing the surface of the magnesium alloy after the treatment in S1.1; S1.3, performing micro-arc oxidation surface treatment on the surface of the magnesium alloy treated in S1.
2.
3. The surface treatment method of magnesium alloy according to claim 2, characterized in that: In S1.2, the degreasing solution used for degreasing includes 2g / L-50g / L sodium hydroxide, 0g / L-2g / L sodium silicate, 1g / L-10g / L sodium carbonate, and 0g / L-30g / L sodium phosphate; the degreasing temperature is 40°C-80°C, and the degreasing time is 2min-10min; The pickling solution used in the pickling includes 5g / L-100g / L organic acid and 0g / L-50g / L sodium nitrate; the organic acid includes at least one of glacial acetic acid, oxalic acid, citric acid, and tartaric acid; the pickling temperature is 30°C-50°C, and the pickling time is 40s-60s; The alkali washing solution used in the alkali washing includes 5g / L-20g / L sodium hydroxide, 0g / L-10g / L sodium tripolyphosphate and 0g / L-10g / L sodium dodecyl sulfate; the alkali washing temperature is 50°C-70°C, and the alkali washing time is 40s-60s.
4. The surface treatment method of magnesium alloy according to claim 2, characterized in that: In S1.3, the electrolyte used in the micro-arc oxidation surface treatment includes 5g / L-40g / L sodium silicate, 5g / L-50g / L sodium hydroxide, 0g / L-10g / L potassium fluoride, 0g / L-30g / L sodium tetraborate and 0g / L-40g / L sodium citrate; The micro-arc oxidation surface treatment adopts a constant voltage mode, a frequency of 600 Hz-1000 Hz, a forward duty cycle of 12%-20%; a treatment temperature below 40° C., and a treatment time of 10 min-30 min.
5. The surface treatment method of magnesium alloy according to claim 1, characterized in that: In S2, the conductive coating includes the conductive high molecular polymer, and S2 specifically comprises: adding a binder to the conductive high molecular polymer and grinding until the mixture is uniformly mixed, adding a first organic solvent, mixing and dispersing the mixture to obtain the conductive coating; the dispersion is performed by stirring or ultrasonic treatment, and the ultrasonic treatment time is 3h-30h; The conductive high molecular polymer includes at least one of polyaniline, polypyrrole and polythiophene; the median particle size of the conductive high molecular polymer is 100nm-500nm; The binder includes at least one of polyvinylidene fluoride, polyacrylonitrile, polyethersulfone, vinyl acetate copolymer, and polyethylene terephthalate; the mass ratio of the conductive polymer to the binder is 1:(0.1-0.3); The first organic solvent is selected from one of xylene, N-methylpyrrolidone, tetrahydrofuran, dimethylformamide, and dichlorobenzene; 3 mL to 10 mL of the first organic solvent is added for every 1 g of the conductive high molecular polymer.
6. The surface treatment method of magnesium alloy according to claim 5, characterized in that: The conductive coating further comprises nano-oxide, and the nano-oxide is selected from at least one of SiO2, ZnO, TiO2, TiN, and MnO2; The nano-oxide is in the form of spherical, flaky, fibrous or irregular particles, with a median particle size of 15nm-60nm; The amount of the nano oxide is 0.5%-3.0% of the total mass of the conductive polymer and the binder.
7. The surface treatment method of magnesium alloy according to claim 1, characterized in that: The conductive coating in S2 includes the carbon nanotubes, and S2 specifically comprises: grinding the carbon nanotubes uniformly, adding a second organic solvent to mix and disperse, so as to obtain the conductive coating; the dispersion is performed by stirring or ultrasonic treatment, and the ultrasonic treatment time is 3h-30h; The second organic solvent is selected from N-methylpyrrolidone or dimethylformamide; 3 mL to 10 mL of the second organic solvent is added for every 1 g of the conductive high molecular polymer. The carbon nanotube has a diameter of 20nm-40nm and a length of 1μm-2μm.
8. The surface treatment method of magnesium alloy according to claim 1, characterized in that: The coating method in S3 is spin coating, dip coating or brush coating; The specific operation steps of the spin coating include: placing the magnesium alloy treated with S1 on the turntable of the coating machine, using a straw to absorb an appropriate amount of the conductive coating dispersed in S2 and dripping it into the middle of the magnesium alloy, starting to spin coat to prepare a film layer, and after the spin coating is completed, taking out the magnesium alloy and placing it in a vacuum drying oven for low-temperature drying; during the spin coating, the spin coating temperature is 5°C-25°C, the rotation speed is 500r / min-1500r / min, and the acceleration is 300m / s 2 -600m / s 2 , the spin coating time is 5s-20s; The specific operation steps of the immersion pulling include: hanging the magnesium alloy treated by S1 on the immersion pulling coating machine, completely immersing it in the conductive coating dispersed in S2, then pulling it out, waiting for natural surface drying, taking out the magnesium alloy and placing it in a vacuum drying oven for low-temperature drying; during the immersion pulling, the magnesium alloy sample needs to keep the bottom of the sample tangent to the liquid surface, the rising speed and the descending speed are 500μm / s-1500μm / s, the immersion time is 60s-300s, the number of coating times is 1-2 times, and the pulling height depends on the sample height and needs to exceed the sample height; The specific operation steps of the brush coating include: placing the magnesium alloy treated with S1 flat on the table, dipping the conductive coating dispersed in S2 with a small brush, and brushing it evenly and evenly on the magnesium alloy until the conductive coating completely covers the micro-arc oxidation film layer, brushing 1 to 3 times, then pulling it out, waiting for natural surface drying, taking out the magnesium alloy and placing it in a vacuum drying oven for low-temperature drying.
9. A magnesium alloy part, characterized in that: The magnesium alloy is prepared by the surface treatment method of any one of claims 1 to 8.
10. Use of the magnesium alloy part according to claim 9 in a proton exchange membrane fuel cell, characterized in that: The magnesium alloy piece is used as a magnesium alloy bipolar plate of a proton exchange membrane fuel cell.
Citation Information
Patent Citations
Aluminum alloy micro-arc oxidization process
CN107557840A
Method for preparing conductive anticorrosive coating on surface of magnesium alloy micro-arc oxidation layer
CN114887858A
Preparation method and application of conductive anticorrosive coating of magnesium alloy bipolar plate
CN116239906A
White micro-arc oxidation electrolyte and preparation method thereof
CN118685833A
A Method Of Coating Magnesium Alloy For Protecting From Corrode
KR1020030040824A
